Learning to Write Argumentation Paragraphs Using the Problem Based Learning (PBL) Model - Niberkati Waruwu; Riana Riana; Agus Kurniawan Hur; Yeni Marlina Telaumbanua (International Journal of Language and Ubiquitous Learning, 2024)
Background. Problem-based learning (PBL) has emerged as an innovative approach in education, particularly in developing critical thinking and writing skills. In the context of learning to write argumentative paragraphs, there is a need to explore the effectiveness of PBL in enhancing students' writing abilities and engagement. Purpose. This study aims to test and analyze the effectiveness of the PBL model in teaching students to write argumentative paragraphs, focusing on topic suitability and content coherence. Method. A qualitative research method with a descriptive approach was employed to identify, describe, and explain the research subjects. The study utilized multiple data collection instruments, including written tests, questionnaires, observations, and interviews. These tools were used to assess students' progress in essay writing and their perceptions of the learning experience. The research was conducted in two cycles to evaluate the implementation and impact of the PBL model. Results. The study found significant improvements in students' performance across the two cycles. In Cycle I, the highest score was 90, the lowest was 70, with an average score of 90. Cycle II showed further improvement, with the highest score reaching 100, the lowest score increasing to 90, and an average score of 100. Conclusion. The findings indicate that the PBL model is effective in enhancing students' ability to write argumentative paragraphs. The marked improvement in scores from Cycle I to Cycle II suggests that the PBL approach contributes to better topic selection, content development, and overall writing quality. This study underscores the potential of PBL as a valuable instructional strategy for developing argumentative writing skills in students.